Wo/man: Our Black Bones of Darkness/light - Fonseca, Dagoberto Jose [UNESP]; Ferreira Fonseca, Simone de Loiola [UNESP]; Teixeira De Jesus, Tarcisia Emanuela [UNESP] (Univ Estadual Paulista-unesp, 2018)
This article aims to approach in an analytical, interpretive and reflexive manner the role of black literature and of the intellectuality that produces it in Brazilian society. It also approaches the sociocultural place of resistance/existence in this creative process, especially in the dynamic and nonlinear trajectory that we can treat identity and memory. The last National Meeting of Black Poets and Fictionists, held in 1987 at SESC in Petropolis (RJ) is our theoretical, epistemic and literary reference. This is the challenge of the black men and women in Brazilian society: informing, denouncing, announcing and inspiring from what they write, because they have always written and inspired so many others such as Gregorio de Matos and Jorge Amado in the past; also to elaborate a literature about black people, as a result of the past experiences that have made them, by crooked lines, denounce the transparent violence that existed in the past, a target of this enslaving, racist, sexist, criminal and xenophobic country - even to the native of the land - and especially to those who built it from the subsoil to the highest and most luxurious skyscraper of the Vieira Souto (RJ) and Paulista (SP) avenues and the Esplanada dos Ministerios (DF).
Keywords: Black literature; Colonialism; Literature of/about black people; Racism; Resistance